Aluminum Alloys and Aluminum-Based Matrix Composites - Di Feng; Qianhao Zang; Ying Liu; Yunsoo Lee (Metals, 2023)
Due to air pollution and energy shortages in the contemporary world, weight lighting for transportation vehicles and energy conservation, as well as emission reductions, are necessary to achieve carbon neutrality and fuel conservation [...]